SANTRIPRENEUR: EDUCATION ON EMPOWERMENT OF STUDENTS THROUGH AGRIBUSINESS ACTIVITIES - Rahmat Fahmi; Asep Saepudin; Eko Sulistiono; Rika Fitri Ramadani (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
This research was motivated by efforts to increase the entrepreneurial skills of students through agribusiness activities in the framework of empowerment. Islamic boarding school is the oldest non-formal educational institution in Indonesia which is engaged in the religious sector. This Islamic boarding school is oriented towards developing the entrepreneurial spirit of the santri with the ultimate goal so that the students can open a business unit and be independent. This study described the implementation of empowerment of students through agribusiness activities related to the input, process, and impact of empowerment This research was used qualitative methods with interview, observation, and documentation techniques. The research findings show that: (1) input for empowerment, namely students, natural resources, curriculum, capital / funds, and partnerships; (2) the empowerment process is carried out through several stages, namely (1) business training; (2) capitalization; (3) assistance; and (4) marketing; (3) the impact of empowerment is that there are many santri alumni of Islamic boarding schools who are independent and able to explore through the management of idle land into agricultural, livestock and fishery areas in increasing the income assets of the established business groups